2017
DOI: 10.1177/0194599817695808
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nasopharyngeal Lymphoma in the United States: A Population‐Based Analysis of 1119 Cases

Abstract: Objectives To describe the incidence and determinants of survival of patients with nasopharyngeal lymphoma (NPL) between 1973 and 2012 using the Surveillance, Epidemiology, and End Results (SEER) database. Study Design Retrospective cohort study using a national database. Methods The SEER registry was used to calculate survival trends for patients with NPL between 1973 and 2012. Patient data were then analyzed with respect to histopathology, age, sex, race, histologic subtype, Ann Arbor stage, and whether radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 40 publications
4
30
3
Order By: Relevance
“…systemic TCL vs. nasal type NK/T cell lymphoma, was provided. Additionally, this fairly large SEER data showed a significantly short overall survival (OS) in NK/T cell lymphoma (13.6 months) (12). The median OS in our study was 36 months, ranging from 4 to 125 months.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…systemic TCL vs. nasal type NK/T cell lymphoma, was provided. Additionally, this fairly large SEER data showed a significantly short overall survival (OS) in NK/T cell lymphoma (13.6 months) (12). The median OS in our study was 36 months, ranging from 4 to 125 months.…”
Section: Discussionsupporting
confidence: 43%
“…One partial, n/a not available study described 62 cases of non-Hodgkin lymphoma of the head and neck region; the majority of which were B cell lymphomas (52 out of 62) with only 7 patients with diagnosis of TCL, including cutaneous forms [11]. Another study focusing on nasopharyngeal lymphoma in 1,119 cases, reported NK/T cell lymphoma comprising only 6% (n = 67) of the cases [12]. However no further sub classification of the TCL, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…WR is not included in the anatomical classification of cervical lymph levels, and is often referred to as an extranodal site of lymphoid tissue. WR is considered the most common extranodal site in the head and neck region in NHL 2,3 . In the pediatric population, WR involvement in NHL is also well described 1,4,5 ; however, involvement of WR in Hodgkin lymphoma (HL) is extremely rare, and is reported almost exclusively in the adult population 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoma, the most common non-epithelial malignancy of the head and neck region, can be classified into two types, Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphoma (NHL) [1]. Among them, primary nasopharyngeal (NP) lymphoma is a very rare tumor, with only limited studies found in the literatures [2,3,4,5,6,7,8,9,10]. Waldeyer-Hartz firstly described the lymphoid tissues within the nasopharynx, oropharyngeal wall, base of the tongue, palatine tonsils, and soft palate, known today as Waldeyer’s ring (WR) [7].…”
Section: Introductionmentioning
confidence: 99%